Modelling high resolution ALMA observations of strongly lensed highly star forming galaxies detected by Herschel - Dye, S.; Furlanetto, C.; Dunne, L.; Eales, S.A.; Negrello, M.; Nayyeri, H.; van der Werf, P.P.; Serjeant, S.; Farrah, D.; Michałowski, M.J.; Baes, M.; Marchetti, L.; et al. (Oxford University Press, 2018)
We have modelled ∼0.1 arcsec resolution ALMA imaging of six strong gravitationally lensed galaxies detected by the Herschel Space Observatory. Our modelling recovers mass properties of the lensing galaxies and, by determining magnification factors, intrinsic properties of the lensed sub-millimetre sources. We find that the lensed galaxies all have high ratios of star formation rate to dust mass, consistent with or higher than the mean ratio for high redshift sub-millimetre galaxies and low redshift ultra-luminous infra-red galaxies. Source reconstruction reveals that most galaxies exhibit disturbed morphologies. Both the cleaned image plane data and the directly observed interferometric visibilities have been modelled, enabling comparison of both approaches. In the majority of cases, the recovered lens models are consistent between methods, all six having mass density profiles that are close to isothermal. However, one system with poor signal to noise shows mildly significant differences.